1994
DOI: 10.1016/0014-5793(94)80422-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor induces acrosomal exocytosis in bovine sperm

Abstract: At the time of fertilization mammalian spermatozoa undergo a Ca2+-dependent exocytotic event, which is known as the acrosome reaction (AR). We describe here that EGF-receptor (EGFR) is localized in the head of bull spermatozoa and that epidermal growth factor (EGF) can induce the occurrence of the AR in its typical dose-dependent manner. Previously we showed that protem kinase C (PKC) is involved in the cascade leading to AR in bull spermatozoa. Here, we show that PKC is involved in the mechanism in which EGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 27 publications
2
42
0
2
Order By: Relevance
“…In regard to the first question, results of studies presented in this report strongly suggest that bFGF increased the PM expression of NHE3 by a selective stimulation of the rate of exit of the exchanger from REC (Table I). Stimulation of exocytosis by growth factors has previously been described for seemingly heterogeneous group of processes like recycling of TfR in human and mouse fibroblasts (30,31), acrosomal exocytosis in bull spermatozoa (32), movement of exocytic vesicles during formation of membrane ruffles in fibroblasts (33), or an EGFinduced acute increase in brush border surface area in rabbit jejunal epithelium (34). It is not clear at this moment whether all of the above processes, including bFGF-stimulated exocytosis of NHE3, share a common regulatory pathway or whether the regulation is protein-or process-specific.…”
Section: Discussionmentioning
confidence: 98%
“…In regard to the first question, results of studies presented in this report strongly suggest that bFGF increased the PM expression of NHE3 by a selective stimulation of the rate of exit of the exchanger from REC (Table I). Stimulation of exocytosis by growth factors has previously been described for seemingly heterogeneous group of processes like recycling of TfR in human and mouse fibroblasts (30,31), acrosomal exocytosis in bull spermatozoa (32), movement of exocytic vesicles during formation of membrane ruffles in fibroblasts (33), or an EGFinduced acute increase in brush border surface area in rabbit jejunal epithelium (34). It is not clear at this moment whether all of the above processes, including bFGF-stimulated exocytosis of NHE3, share a common regulatory pathway or whether the regulation is protein-or process-specific.…”
Section: Discussionmentioning
confidence: 98%
“…effect on freshly isolated boar sperm (Oliva-Hernandez and Perez-Gutierrez 2008), manifested inhibiting effect on fresh human sperm (Naz and Kaplan 1993) and stimulating effect for mouse, human (Furuya et al 1993a,b) and bovine (Lax et al 1994) sperm functions in vitro. The absence of EGF effect on boar sperm function may be explained by the fact, that in this species not all the sperm cells can bear EGF receptors (Oliva-Hernandez and Perez-Gutierrez 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of EGF in plasma of mouse males led to the decrease in sperm concentration and motility (Liu et al 1994), whilst the administration of exogenous EGF was useful for repair of testicular disorders (Uguralp et al 2004;Kurokawa et al 2005) or for the treatment of male infertility in rodents (Cheng et al 2006). EGF regulates sperm functions (capacitation, acrosome reaction) through the activation of tyrosine kinase (Furuya et al 1993a;Naz and Kaplan 1993) or protein kinase C (Lax et al 1994), which are activated by specific EGF receptors demonstrated in several animal species (Naz and Ahmad 1992;Naz and Minhas 1995;Oliva-Hernandez and Perez-Gutierrez 2008). These observations suggest that EGF could be potentially used for the improvement of sperm characteristics in farm animal breeding and assisted reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…We showed previously that bovine sperm contains EGFR localized to the sperm head and the mid-piece (50,52). It also has been shown that EGFR is involved in the AR and in actin polymerization during sperm capacitation (39,50,52). Moreover, EGFR phosphorylation/ activation is increased during capacitation.…”
mentioning
confidence: 90%
“…The activation of the EGFR generates a Ca 2ϩ signal, broadly defined as the transient rise of the intracellular concentration of Ca 2ϩ (51). We showed previously that bovine sperm contains EGFR localized to the sperm head and the mid-piece (50,52). It also has been shown that EGFR is involved in the AR and in actin polymerization during sperm capacitation (39,50,52).…”
mentioning
confidence: 99%